2001
DOI: 10.1053/euhj.2000.2428
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve in angiographically normal coronary arteries with one-vessel coronary artery disease without traditional risk factors

Abstract: Coronary flow reserve is preserved in regions supplied by angiographically normal coronary arteries with one-vessel coronary artery disease without traditional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…6,7 Other studies have described an impairment of vasomotor tone of the angiographically normal coronary artery and remote CAD only in patients with coronary risk factors. 8 In our series, all patients with angiographically normal LAD, remote CAD, and no myocardial infarction had a CFR in the LAD within the range of the control group ( Figure 1 and Table 1), which was also independent of risk factors (see confidence intervals in Figure 1) and number of vessels with disease.…”
Section: Discussionmentioning
confidence: 81%
“…6,7 Other studies have described an impairment of vasomotor tone of the angiographically normal coronary artery and remote CAD only in patients with coronary risk factors. 8 In our series, all patients with angiographically normal LAD, remote CAD, and no myocardial infarction had a CFR in the LAD within the range of the control group ( Figure 1 and Table 1), which was also independent of risk factors (see confidence intervals in Figure 1) and number of vessels with disease.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, coronary vascular dysfunction may occur in the absence of any angiographically detectible epicardial atherosclerosis. 52,59,60 Abnormalities of coronary vascular function have been demonstrated in a variety of disease states known to be associated with accelerated coronary atherosclerosis without overt cardiovascular disease including hypertension, 61 dyslipidemia, 62,63 tobacco abuse, 64,65 obesity, 66,67 metabolic syndrome, 68 diabetes, 6971 and renal dysfunction. 72 As such, vascular dysfunction represents the earliest form of atherosclerosis, preceding the development of obstructive stenoses that are detectible by traditional imaging modalities, 64,70,73,74 including coronary calcium scoring.…”
Section: Quantitative Mbf For Diagnosis Of Obstructive Cadmentioning
confidence: 99%
“…59 In some cases, such failure to adequately vasodilate may be sufficient to cause myocardial ischemia even in the absence of epicardial obstructive disease. 7678 Because the underlying process in these cases is diffuse atherosclerosis and/or endothelial dys-function, affecting all or most of the coronary tree, regional perfusion abnormalities may be difficult in identifying traditional semi-quantitative approaches.…”
Section: Quantitative Mbf For Diagnosis Of Obstructive Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…MBF and MPR are globally reduced also in the remote myocardium supplied by angiographically normal coronary arteries in patients with significant CAD elsewhere (10). However, Fujiwara et al found preserved MPR in regions supplied by angiographically normal coronary arteries in patients with 1-vessel CAD without coronary risk factors (16). It is possible that angiographically undetectable atherosclerosis and endothelial dysfunction, associated with the presence and severity of coronary risk factors, could be responsible for a blunted MPR in patients with or without evident CAD (17).…”
Section: Pet-measured Mpr: a New Target Of Treatmentmentioning
confidence: 99%